Comparing the meningococcal serogroup C immune response elicited by a tetanus toxoid conjugate quadrivalent meningococcal vaccine (MenACYW-TT) versus a quadrivalent or monovalent C tetanus toxoid conjugate meningococcal vaccine in healthy meningococcal vaccine-naïve toddlers: A randomised, controlled trial. Issue 5 (30th November 2022) - Knuf, Markus; Rämet, Mika; Breinholt Stærke, Nina; Bertrand-Gerentes, Isabelle; Thollot, Yaël; B'Chir, Siham; Arroum, Habiba; Oster, Philipp
ABSTRACT: MenACYW-TT (MenQuadfi®) is a quadrivalent meningococcal tetanus toxoid conjugate vaccine licensed in Europe for use in individuals ≥12 months. This study assessed whether serogroup C immune responses with MenACYW-TT were at least non-inferior, or superior, to those of quadrivalent meningococcal ACWY (MCV4-TT; Nimenrix®) and monovalent meningococcal C (MenC-TT; NeisVac-C®) vaccines in toddlers (12–23 months). In this modified, double-blind Phase III study (NCT03890367), 701 toddlers received one dose of MenACYW-TT (n = 230), MCV4-TT (n = 232) or MenC-TT (n = 239). Serum bactericidal assays with human (hSBA) and baby rabbit (rSBA) complement were used to measure anti-meningococcal serogroup C antibodies at baseline and 30 days post-vaccination. A sequential statistical approach was used for primary and secondary objectives. For the primary objectives, superiority of serogroup C was assessed in terms of hSBA seroprotection rates (defined as titers ≥1:8) and GMTs for MenACYW-TT compared to MCV4-TT, and rSBA GMTs compared to MenC-TT. The safety of all vaccines within 30 days post-vaccination was described. When administered as a single dose to meningococcal vaccine-naïve healthy toddlers the superiority of the MenACYW-TT serogroup C immune response versus MCV4-TT was demonstrated for hSBA GMTs (ratio 16.3 [12.7–21.0]) and seroprotection (difference 10.43% [5.68–16.20]); and versus MenC-TT in terms of rSBA GMTs (ratio 1.32 [1.06–1.64]). The safety profiles of a single dose of MenACYW-TT, MCV4-TT and MenC-TT were similar. In meningococcal vaccine-naïve toddlers, MenACYW-TT induced superior immune responses to serogroup C versus MCV4-TT in terms of hSBA seroprotection and GMTs and versus MenC-TT in terms of rSBA GMTs.